HYDROGELS BASED ON 2-HYDROXYETHYL METHACRYLATE: SYNTHESIS, CHARACTERIZATION AND HYDRATION CAPACITY - Oyarce, Estefanía; Pizarro, Guadalupe del C.; Oyarzún, Diego; Zúñiga, César; Sanchez, Julio (Journal of the Chilean Chemical Society, 2020)
In the present work, three hydrogels of poly(2-hydroxyethyl methacrylate-co-itaconic acid), p(HEMA-co-IA), poly(2-hydroxyethyl methacrylate-co-acrylic acid), p(HEMA-co-AA) and poly(2-hydroxyethyl methacrylate-co-(1-vinyl-2-pyrrolidone)), p(HEMA-co-NVP) were prepared by free radical polymerization in aqueous solution (1:1 monomer mole ratio) using ammonium persulfate as initiator and N,N´-methylenebisacrylamide as crosslinking agent at two different amount (0.3 and 0.9 mol%). The obtained hydrogels were characterized by Fourier transform infrared spectroscopy (FT-IR), which allowed to verify the structural composition. Thermal analysis of the hydrogels was carried out by thermogravimetric analysis (TGA). In addition, hydration capacity (U%) was studied at different experimental conditions such as: time, pH, concentrations of interfering salts (KCl, NaCl and LiCl). The results showed a good polymerization yield (95%). FTIR characterization shows the absorption bands of the functional groups of copolymers. TGA exhibited the characteristic thermal stability of this type of hydrogels. The presence of comonomer AI, AA or NVP in copolymer determine the thermal behavior. Hydration experiments revealed a higher U% in copolymer containing more carboxylic acid groups. The maximum U% values in water were 400% and 250% for p(HEMA-co-AI) and p(HEMA-co-AA), respectively. For P(HEMA-co-NVP) a maximum of U% value was only 74% in water. The effect of interferent salts affects the hydration capacity decreasing U% when the concentration of salts increase.